From scientist to academic developer: A story - Bailey, Tracey (Taylor and Francis, 2023)
When I started in Higher Education [HE] as a Lecturer in Biomedicine in 2002, I thought a good teacher was someone who could present their subject in an interesting manner in a PowerPoint presentation for an hour. My approach to assessment was based on the academic essays and examinations I had struggled with as a student. Through the parallel processes of being a Course Director and taking a Postgraduate Certificate [PGCert] in HE, I realised that this approach was not only far from true, but the tip of a very complex iceberg. The way I thought about students, their development, their assessment, and the support they needed to reach their potential was transformed through an inspiring developer and conversations with my peers. Collectively, we were passionate about making a difference to students at our University, and although the size of the iceberg was daunting, we were determined to chip away at it and make a difference.